¿Cómo se funda un convento? Algunas consideraciones en torno al surgimiento de la vida monástica femenina en Santa Fe de Bogotá (1578-1645) (2017)
The spanish crown, with the control of the patronage, had the economical obligation of maintaining the evangelization of the new world; That also implied the establishment of abbeys. It wasn’t the same with the womens’ convents, considered ‘pious works’ which owe be promoted by the bishops and laymen. In this essay we analyzed the opening process of three femenine convents in the New kingdom of Granada: Santa Clara (Tunja), Nuestra Señora de la Concepción and Santa Inés (santafé). From the analysis of documentary sources we pretend to answer who were the founders, why did they decided to rise a women’s convent, how much was the investment and how the opening was managed. Thus we pursue to highlight social strategies that associate the religious affiliations and the elites’ economy between the late 16th and first half of the 17th century.